Drawing Processes of Life Molecules, Cells, Organisms - Anderson-Tempini, Gemma; Dupré, John (2023)
How the challenge of depicting biological systems can generate productive questions for artists and scientists. An artist drawing cell division faces a problem: what is the best way to visually represent a dynamic process? This anthology, edited by an artist and a philosopher of science, explores drawing as a way of inquiring into living processes at the molecular, cellular, and organismal scale. In doing so, drawing emerges as a tool for relaying and uncovering knowledge - a pathway for research, not an end result. Incorporating drawing studies and contributions from schol- ars in the humanities and life sciences, Drawing Processes of Life addresses epistemological issues arising in cell division, insect metamorphosis, protein folding, and other ever-shifting biological systems. Fulfilling the promise of an interdisciplinary collaboration between artists and scientists, this book demonstrates the interweav- ing of processes, scientific, artistic, and non-human that the abstractive techniques of modern science so readily obscure.